Development of Identification Algorithms in Frequency Domain for Friction-Based Servo Drives Technology - Aung, Lwin Mar (IJRDO - Journal of Electrical And Electronics Engineering, 2019)
In this paper, nonlinearities, such as friction, backlashes, and saturations are commonly exists in servo drive systems in industry. Specifically, friction exists in servo motor control systems. The friction effects are undesirable in servo applications because they disturb the system performance. So it is required to know or identify the friction in servo systems. In this thesis, binary test signals are used to perform identification, thus simplifying the behaviour of friction. An identification method using the Identification Toolbox in MATLAB/SIMULINK is proposed in this analysis.